Penggunaan Aplikasi Canva sebagai Media Pembelajaran Interaktif untuk Meningkatkan Keaktifan Siswa SMP Bank Saller Hewokloang - Yuyun Sutari; Nur Auliya; Monika Hediana Tanga; Nur Iftitah (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study aims to analyze the use of Canva-based learning media in improving student engagement at SMP Bank Saller. The study is motivated by the low level of student engagement caused by teacher-centered learning practices and the underutilization of available technological facilities in schools. This research employed a descriptive qualitative approach involving 15 students as research subjects. Data were collected through observation, interviews, and documentation during the learning process. The results indicate that prior to the use of Canva, students tended to be passive, showed low participation in discussions, and lacked motivation in learning activities. After the implementation of Canva-based learning media, there was a significant improvement in student engagement, as reflected in increased participation in discussions, greater willingness to ask questions, and higher enthusiasm in learning. Canva contributed to creating a more engaging, interactive, and enjoyable learning environment due to its attractive visual features and user-friendly interface. In conclusion, the use of Canva-based learning media is effective in enhancing student engagement. This study recommends that teachers integrate technology into their teaching practices and develop innovative learning media to improve the quality of the teaching and learning process.